Endocrine Late Effects in Young Cancer Patients: Thyroid Gland - Brabant, Georg; Dörr, Helmuth-Günther (Springer International Publishing, 2020)
The increased survival rates after pediatric oncological therapy result in an increase in the number of patients showing late effects of tumor therapy. Thyroid function and proliferation disorders in particular are common sequelae of treatment of malignant tumors in childhood and adolescence. They predominantly occur after irradiation of the head and neck and the thyroid glands. The clinical symptoms depend on the thyroid hormone status. The current guidelines on endocrine late effects in these patients are endorsed by the working group of the Scientific Medical Specialist Societies (AWMF). Based on standardized evaluation of currently available literature, this review article summarizes the approaches for late sequelae of tumor therapy on thyroid glands. The specific group of long-term survivors of younger ages, like children, adolescents, and young adults, are constantly growing due to enhanced diagnostic tools and more effective treatment strategies. Thus, their specific survivorship care needs to be addressed in a holistic approach. Whilst a lot of scientific work has focused on somatic late effects of survivors, a growing body of research has recently been directed towards psychosocial outcomes of survivors. A part of them are reaching psychosocial stability after they had overcome the cancer disease and its treatment. In the following chapter, we aim to point out social outcomes of survivors and risk factors for adverse outcomes. The latter thus define subgroups for intensified follow-up and care. An early identification of groups at high risk is crucial, in order to understand, and later prevents the pathways leading to poor socioeconomic outcomes. We also provide information how reintegration into everyday life takes place, i.e., which challenges are faced and how they may be overcome.
CRIS-Team Scopus Importer:2024-12-16